Review of Mavacamten for Obstructive Hypertrophic Cardiomyopathy and Future Directions - Dong T; Alencherry B; Ospina S; Desai MY (Dove Medical Press, 2023)
Tiffany Dong,* Ben Alencherry,* Susan Ospina, Milind Y Desai Section of Cardiovascular Imaging, Heart, Vascular and Thoracic Institute, Cleveland Clinic, Cleveland, OH, USA*These authors contributed equally to this workCorrespondence: Milind Y Desai, Department of Cardiovascular Medicine, Miller Family Heart and Vascular Institute, Cleveland Clinic Main Campus J1-5, 9500 Euclid Avenue, Cleveland, OH, 44195, USA, Tel +1 216 445 5250, Fax +1 216 445 6155, Email desaim2@ccf.orgAbstract: Hypertrophic cardiomyopathy (HCM) is a condition with abnormal hypertrophy of the left ventricle in the absence of common causes. The most common form involves the basal septum and can lead to obstruction of the left ventricular outflow tract. Patients can experience exertional symptoms such as chest pain, dyspnea and syncope. Traditional treatment has included beta blockers and nondihydropyridine calcium channel blockers with second-line therapy being disopyramide. Recently, mavacamten, a cardiac myosin inhibitor, has demonstrated improvement in quantitative measures of obstruction and symptom relief to such a degree that patients were able to defer invasive management of the disease. This review focuses on the pharmacology of mavacamten, its clinical trial data and guidance on how to incorporate this drug into clinical practice. Furthermore, it discusses emerging therapies currently being investigated for HCM.Keywords: hypertrophic cardiomyopathy, mavacamten, septal reduction therapy, EXPLORER HCM, VALOR HCM